Relación entre intención emprendedora, aspiraciones y satisfacción con la vida en universitarios limeños - Paredes Juárez, María Cristina (2015)
This study's main objective is to know the relationship between entrepreneurial intention, intrinsic and extrinsic aspirations and satisfaction with life in university students from the International Business career of a private university in Lima. The sample is represented by 222 students, 88 men and 134 women, with an average age of 21 years and between the third and tenth semester of university. Three instruments were used, the Entrepreneurial Intention Questionnaire (Linan & Chen, 2004) adapted by Liza (2011), the reduced Aspirations Index (Duriez, Vansteenkiste, Soenens & De Wine, 2007) and the Satisfaction with Life Scale (Diener, 1985) adapted by Alarcon (2000). The study found that there is significant positive correlation (p <.001) between Entrepreneurial Intention and Aspirations (Intrinsic and Extrinsic) and between Life Satisfaction and Intrinsic Aspirations. It also found a positive relationship between Entrepreneurial Intention and Life Satisfaction (p <.05). Although entrepreneurial intention didn’t predict satisfaction with life, it was found that controlling the variables of semester, work experience and extrinsic aspirations, the intrinsic aspirations are a significant predictor (β = .22, p <.01) of Satisfaction with Life and Entrepreneurial Intention.